Hubungan Emotional Eating dan Aktivitas Fisik Terhadap Kejadian Obesitas di Madrasah Ibtidaiyah Nashrul Fajar Semarang - Annisa Risqi Amaliya Putri; Amin Samiasih; Hema Dewi Anggraheny (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Childhood obesity is a growing health problem and is influenced by various factors, including eating behavior and physical activity. Emotional eating can encourage food consumption in response to emotional conditions, while physical activity plays a role in energy expenditure. This study aims to analyze the relationship between emotional eating and physical activity with obesity in students at Madrasah Ibtidaiyah Nashrul Fajar Semarang. This study used a quantitative method with an observational analytic design and a cross-sectional approach. The sample consisted of 40 sixth-grade students selected using a purposive sampling technique. Emotional eating data were measured using the Dutch Eating Behavior Questionnaire (DEBQ), while physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C). The results showed that 55% of respondents were obese, 57.5% showed no tendency to emotional eating, and 47.5% had low physical activity. The Spearman correlation test showed a significant positive relationship between emotional eating and obesity (p=0.018; r=0.371), with a low to moderate strength of the relationship. Meanwhile, physical activity was not significantly associated with obesity (p=0.229; r=-0.195), although it showed a weak negative relationship. Thus, emotional eating is associated with obesity, while physical activity did not show a significant association among the respondents in this study.